L’arabe à l’école : Hiérarchie des mobilités géographiques, inégalités des conditions linguistiques - Éric Soriano (Recherches en didactique des langues et des cultures)
This paper proposes to describe some recent achievements of the sociology of the school applied to students with an immigrant background. It questions the trajectory of these children for whom, from kindergarten to secondary school, the school is also a language school (French), but whose situation is rarely identified as such. It shows the effects of a context in which the Arabic language is caught between parental impotence and unthought of institution.